Multi-function screening of probiotics to improve oral health and evaluating their efficacy in a rat periodontitis model - Nie, Qingqing; Wan, Xuchun; Tao, Hua; Yang, Qianqian; Zhao, Xueyang; Liu, Haixia; Hu, Jun; Luo, Yanan; Shu, Ting; Geng, Ran; Gu, Zhijing; Fan, Fengkai; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The oral cavity is the second most microbially rich region of the human body, and many studies have shown that there is a strong association between microorganisms and oral health. Some pathogenic bacteria produce biofilms and harmful metabolites in the mouth that may cause oral problems such as oral malodor, periodontitis, and dental caries. Altering the oral microbiota by using probiotics may alleviate oral health problems. Thus, using multi-function screening, we aimed to identify probiotics that can significantly improve oral health. The main parameters were the inhibition of pathogenic bacteria growth, inhibition of biofilm formation, reduction in the production of indole, H2S, and NH3 metabolites that cause halitosis, increase in the production of H2O2 to combat harmful bacteria, and co-aggregation with pathogens to prevent their adhesion and colonization in the oral cavity. Tolerance to cholic acid and choline was also assessed. Bifidobacterium animalis ZK-77, Lactobacillus salivarius ZK-88, and Streptococcus salivarius ZK-102 had antibacterial activity and inhibited biofilm production to prevent caries. They also improved the oral malodor parameter, H2S, NH3, and indole production. The selected probiotics (especially L. salivarius ZK-88) alleviated the inflammation in the oral cavity of rats with periodontitis. The analysis of the gingival crevicular fluid microbiome after probiotic intervention showed that B. animalis ZK-77 likely helped to restore the oral microbiota and maintain the oral microecology. Next, we determined the best prebiotics for each candidate probiotic in order to obtain a formulation with improved effects. We then verified that a probiotics/prebiotic combination (B. animalis ZK-77, L. salivarius ZK-88, and fructooligosaccharides) significantly improved halitosis and teeth color in cats. Using whole-genome sequencing and acute toxicity mouse experiments involving the two probiotics, we found that neither probiotic had virulence genes and they had no significant effects on the growth or development of mice, indicating their safety. Taking the results together, B. animalis ZK-77 and L. salivarius ZK-88 can improve oral health, as verified by in vivo and in vitro experiments. This study provides a reference for clinical research and also provides new evidence for the oral health benefits of probiotics.